Perancangan UI/UX Website Penjualan Ikan Hias Pada Toko AW Aquascape Menggunakan Metode Keep It Simple - Sofyan Mufti Prasetiyo; Adi Maulana; Rizhar Hakiki; Tuti Alawiyah (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Website is an information page that is provided via the internet so that it can be accessed throughout the world as long as it is connected to the internet network. Sales websites can be used to promote goods and services that are sold online where the transaction process is also done online. The sales website at AW Aquascape is one of the promotional media they use to offer their products. To achieve the promotional objectives through the sales website, a good User Interface (UI) and User Experience (UX) design is needed so that users are comfortable using it and the user will be interested in buying the products being sold. This journal contains an explanation of how the UI/UX is designed on the AW Aquascape sales website using the Keep It Simple Stupid method. This study aims to design UI/UX planning on the AW Aquascape sales website. The final result of this study is the design of a UI/UX design for the AW Aquascape sales website that is effective and efficient for users to use. The research process consisted of several stages, namely making a user interface design using the keep it simple stupid method which in making a design, the most important thing is simplicity and does not contain any elements of complexity. This method prioritizes making designs that are as simple as possible, but has a good appearance, and supports an effective user experience.